IPTEKS PERHITUNGAN POTENSI PENERIMAAN PAJAK HOTEL TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN MINAHASA UTARA - Christian, Pongtuluran Andri (Universitas Sam Ratulangi, 2017)
The implementation of autonomy for the local government drive the efforts to explore their own financial resources and potential tax revenue. The local government has authority, rights and obligation to manage finance,Â infrastructure and human resource. It is important for local government to find out the tax potency to set a revenue target for next period, as a part of government planning. The method used is calculating the potential of hotel tax revenues to Local Own Source Revenue (PAD) in North Minahasa Regency. The technique applied is calculating the increase in the realization of potential hotel taxes each year and the average rate of increase in hotel tax potential. After calculate Â the Increase in Realization of Each Year, and the average rate of increase, the result of potential hotel tax in North Minahasa Regency. is Rp. 3,285,398,969,531.2. at 2016.